In-vitro Studies on Copper Nanoparticles and Nano-hydroxyapatite Infused Biopolymeric Composite Scaffolds for Bone Bioengineering Applications - Kumari S.; Mishra A.; Singh D.; Li C.; Srivastava P. (My University, 2025)
This research study deals with the development of copper nanoparticles (CN) and nano-hydroxyapatite (nHAP) infused chitosan (C) and gelatin (G) based nanocomposite scaffolds for bone tissue engineering applications. Human-origin osteoblast cells (MG-63) were seeded over the scaffolds to investigate the novel biomimetic extracellular matrix system. The scanning electron microscopy (SEM) showed an average pore size between 100–146 µm for all the C-G-nHAP-CN based scaffolds. The in-vitro degradation study showed 74–83% degradation for CN-based scaffolds. For 0.03% CN based scaffold degradation rate (84%) was very close to the control scaffold. Swelling ratio was highest for the chitosan scaffold and it was in the range between 5.25–5.93 mg/mL for other scaffolds. Compressive moduli were highest for 0.03% CN scaffold (3.32 MPa) which was relatively very high in comparison to C-G-nHAP scaffold with 2.4 MPa strength in a wet state. Stress-strain graphs also show the maximum displacement by 0.03% CN scaffold. The functional and structural analysis for the scaffolds showed the presence of nHAP in the scaffold and CN peaks within the composite structure. Differential scanning colorimetry testing showed reduced crystallinity in CN-based scaffolds with a melting temperature of 320°C. Their 2D cell behaviour in the Electrical Cell Impedance System (ECIS) study showed maximum cell spreading and growth in 0.02% CN-based scaffold. The cell-seeded composite was tested for 3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide (MTT), 4,6-diamidino-2-phenylindole (DAPI), and acridine orange and propidium iodide (AOPI) assay for testing its cytocompatibility for MG-63 cell line. Cell proliferation and cell spreading was observed by SEM in all the CN-based scaffolds. Alkaline phosphatase (ALP) activity was highest in 0.03% CN scaffold with 2.0 optical density (OD) value. Alizarin Red Stain (ARS) staining was performed to support this study. It can be statistically depicted that nHAP and 0.03% CN-based scaffold could be potential biomaterial for minor to severe bone-related tissue regeneration applications. © 2023, The Korean Society for Biotechnology and Bioengineering and Springer.